Edukasi QS. Ar-Rum: 41 Melalui Budidaya Maggot dan Rocket Stove via Komunikasi Lingkungan: Education of QS. Ar-Rum: 41 Through Maggot Cultivation and Rocket Stove via Environmental Communication - Muhammad Hasbi A Suarsyaf; Desi Maharani; Reza Ardhika; Silvia Wulandari (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This community service activity aims to enhance the ecological awareness of the residents of Kanoman Village, Cibeber District, Cianjur Regency, through the integration of the spiritual values of QS. Ar-Rum: 41 with appropriate technologies, namely maggot cultivation and rocket stove construction. The main problems faced by the partners are the low public awareness in managing household waste, especially organic and plastic waste, as well as the absence of a sustainable community-based waste management system. The implementation method used the Participatory Action Research (PAR) approach, involving 12 students and village residents alternately for 45 days (July 7 – August 20, 2026). Activities included the socialization of Qur'anic values on environmental conservation, maggot cultivation education starting from attracting BSF flies to harvesting, and the collective construction of a rocket stove from used drums behind the head of village's office. The results showed an increase in residents' understanding of the relationship between environmental damage and human actions from 20% to 80%, maggot production of 1-2 kg per week used as animal feed, and one unit of rocket stove capable of reducing waste mass by up to 98% with only 2% ash residue. This program was inaugurated and handed over to the village government to be managed independently by the residents. This activity proves that an approach based on religious values, active community participation, and simple technologies using local materials can create a sustainable and empowering waste management program.